Peculiarities of conflict behavior in younger and older adolescents (Actual Problems of Psychology in Educational Institutions, 2020)
Abstract. The article is devoted to the analysis of the problem of detectingconflict behavior in adolescence. The author outlines the content of conflictand conflict situation, discusses the main causes of conflict, makes acomparative analysis of constructive and destructive conflicts, states bothpositive and negative functions of conflicts, describes different styles ofbehavior in conflict situation. There is clarified that characteristic ofadolescence is an increase in the proportion to problematic behaviors inconflict.The article presents the results of an empirical study pointing to changesin styles of conflict behavior during the process of becoming an individual,in particular the tendency to increase the use of oppositional patterns ofbehavior, activity in the fight against constant customs and laws, increasingenvy and hatred to others
Keywords: conflic; conflict style of behavior; conflict strategy of behavior; aggressiveness; hostility